Highly Pathogenic Avian Influenza Virus (H5N8) Clade 2.3.4.4 Infection in Migratory Birds, Egypt - Selim, Abdullah A.; Erfan, Ahmed M.; Hagag, Naglaa; Zanaty, Ali; Samir, Abdel-Hafez; Samy, Mohamed; Abdelhalim, Ahmed; Arafa, Abdel-Satar A.; Soliman, Mohamed A.; Shaheen, Momtaz; Ibraheem, Essam M.; Mahrous, Ibrahim; et al. (Emerging infectious diseases, 2017)
We isolated highly pathogenic avian influenza virus (H5N8) of clade 2.3.4.4 from the common coot (Fulica atra) in Egypt, documenting its introduction into Africa through migratory birds. This virus has a close genetic relationship with subtype H5N8 viruses circulating in Europe. Enhanced surveillance to detect newly emerging viruses is warranted.